Dr. Heri Noviana — Deep Plane Facelift — Jakarta - Noviana, Heri (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Heri Noviana, practicing in Jakarta, Indonesia. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003263; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; indonesia; jakarta